MANAJEMEN PENINGKATAN MUTU LEMBAGA PENDIDIKAN ISLAM - Hilman Wadjdi (Ta`Limuna: Jurnal Pendidikan Islam, 2012)
Advance quality in education sector, including quality in input, process, output, and outcome, is very important to get serious attention from every element of educational institution. Because with increase their education quality, the education institution will have competence and become favourite institution in education customers (student parent and society). The education institution which continually keeps its quality will always take correcting, developing, and innovation in education quality, so it, their services, result and performances are continually increased and automatically the school/university will be favourite ones.